Neutron scattering with a triple-axis spectrometer : - Shirane, G. (Cambridge University Press, 2002)
Shirane, Stephan Shapiro, and John Tranquada describe the basic techniques for using the triple-axis spectrometer to analyze neutron scattering that they have developed at Brookhaven National Laboratory, New York from 1965 to 1996. They say the equipment has played a major role in the success of the High Flux Beam Reactor there, and has generally been a most versatile instrument in many areas of condensed- matter science. They hope the information will be useful to graduate students, beginning researchers, and experienced researchers new to neutron scattering.